Implementation of Law Number 6 of 2011 concerning Immigration in the Immigration Work Unit of Bojonegoro Regency - Utama, Cornelia Yashela; Sudja, Sudja; Hardyansah, Rommy (IHSA Institute, 2024)
Implementing passport services in the Immigration Work Unit of Bojonegoro Regency has shown significant efforts in implementing Law Number 6 of 2011 concerning Immigration. This is reflected in the implementation of an online application system, strict document verification, the use of biometric technology, and high document security standards. This work unit has also improved service efficiency through an integrated management information system, special services for certain groups, and increased transparency and accountability. However, there is still room for improvement and optimization to meet the expected service standards. This study aims to analyze passport services in the Immigration Work Unit of Bojonegoro Regency and identify inhibiting factors in implementing passport services. The method in this study is empirical law by examining Law Number 6 of 2011 concerning Immigration in the Immigration Work Unit of Bojonegoro Regency. The results of this research are that the implementation of passport services in the Immigration Work Unit of Bojonegoro Regency has shown significant efforts in implementing the principles of Law Number 6 of 2011. This work unit seeks to improve service efficiency through the implementation of an integrated management information system and the provision of special services for certain groups; the factors inhibiting the implementation of passport services include a shortage of human resources in terms of quantity or quality, technological infrastructure that sometimes experiences disruptions, bureaucratic procedures that still need to be simplified.